2017
DOI: 10.3991/ijim.v11i1.6420
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Learning Apps in Instruction And Students Achievement

Abstract: Abstract-Mobile learning technique is increasingly popular and is acting as a good instructional medium , How mobile learning apps enhances students achievement is investigated in this study. The students were divided in to two group and experimented. The result indicated that the students achievement is higher in the group who made use of mobile apps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 4 publications
1
13
0
1
Order By: Relevance
“…Mobile devices such as laptops and smartphones are now a potential learning media (Sung, Chang, & Liu, 2016) and proven ability to improve student learning achievement (Kattayat, Josey, & Asha, 2017). This is related to the development of wireless technology and various mobile device innovations that make it easy for students to study wherever and whenever (Sung, Chang, & Yang, 2015;Chinnery, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mobile devices such as laptops and smartphones are now a potential learning media (Sung, Chang, & Liu, 2016) and proven ability to improve student learning achievement (Kattayat, Josey, & Asha, 2017). This is related to the development of wireless technology and various mobile device innovations that make it easy for students to study wherever and whenever (Sung, Chang, & Yang, 2015;Chinnery, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Before this study there was a study by Karabatzaki et al, (2018) about Mobile learning for preschool where it was stated that children's cognitive skills development with digital media and have well-designed mobile-based learning activities and games could improve skills of abstract thinking, reflective thinking, and analyzing and evaluating Kattayat, Josey, & Asha (2017) found that the results show that teaching learning processes using mobile apps are helpful to students in improving their learning achievements. In the first mathematics mobile learning application that was developed using the ExeLearning 2.0 program seen in the results of validation according to Table 5 stated that in display and material, this application met the criteria very well.…”
Section: Discussionmentioning
confidence: 99%
“…Kattayat in 2017 conducted research on the implementation of mobile learning in a number of students. The results showed that learning techniques with mlearning could improve achievement [20].…”
Section: A Mobile Learningmentioning
confidence: 99%